How does high-commitment work systems stimulate employees’ creative behavior? A multilevel moderated mediation model - Zhang, Min; Chen, Zhihong; Zhao, Lijing; Li, Xiang; Zhang, Zhi; Zhang, Xufan (Frontiers in Psychology, 2022)
How to effectively stimulate employees’ creative behavior is a hot topic in the field of organizational behavior. Based on conservation of resources theory and substitutes for leadership theory, this paper discusses the impact of high-commitment work systems on employees' creative behavior and the roles of employees' well-being and CEO inclusive leadership. By constructing a cross-level structural equation model and analyzing the paired data of 86 CEOs, 86 HR managers and 489 employees, the results show that: (1) high-commitment work systems have positive impact on employees' creative behavior; (2) employee’s well-being mediates the process of high-commitment work systems driving employees' creative behavior; (3) CEO inclusive leadership negatively moderates the relationship between high-commitment work systems and employees’ well-being, and further negatively moderates the indirect effect of high-commitment work systems on employees’ creative behavior through employees’ well-being, that is, the lower the level of CEO inclusive leadership is, the stronger the impact of high-commitment work systems on employees’ creative behavior through employees’ well-being will be.